Pengaruh Harga, Cadangan Devisa, Dan Jumlah Penduduk Terhadap Impor Beras Indonesia - Dwipayana, I Kadek Agus; Kesumajaya, Wayan Wita (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 3, No. 4, April 2014 (pp. 124-172), 2014)
Rice is the main food for people in Indonesia. Demand for rice in Indonesia is so high. Therefore, to meet this demand Indonesia has to import its rice from another country. If a country import its stuffs from another country that means this country has a good growing economic condition. The purpose of import is to supply basic commodities or consumer goods, purchases of raw materials for industry in the country, and for the procurement of capital goods that cannot be produced in the country itself. The purpose of this paper was to determine the effect of prices, foreign exchange reserves, and number of population against Indonesian’s rice import in the period 1997-2012 by using multiple linear technical analyses. The results of this study indicating that the price, foreign exchange reserves, and population simultaneously effected on rice imports in Indonesia from 1997 to 2012 significantly. Partially prices had positive influence and foreign exchange reserves had a significant positive effect, while number of population did not effect on Indonesian rice imports in the period 1997-2012.
Keywords: Import; World Price; Foreign Exchange Reserves; and Population